The importance of rheological parameters in the therapy of microcirculatory disorders - Bláha, M; Rencová, E; Bláha, V; Malý, R; Blazek, M; Studnicka, J; Andrýs, C; Fátorová, I; Filip, S; Kasparová, M; Procházková, R; Malý, J; et al. (Clinical hemorheology and microcirculation, 2009)
Rheological conditions basically influence tissue perfusion, oxygen and nutrient supply, tissue regeneration and in its consequence the course of pathological processes, especially in microcirculation and partially even in macrocirculation. Haemorheotherapy has shown to be successful in several indications (critical disorders in microcirculation) when other methods of therapy have failed. In this study we describe the changes of effectivity indicators in haemorheopheresis treatment and their clinical importance in cases of eye microcirculation, statoacoustic apparatus and disorders of the lower extremities. We treated with haemorheopheresis (separator Cobe.Spetra + Evaflux filter) 24 patients (16 patients with age related macular degeneration, 5 with critical peripheral arterial foot disease, and 3 with acute hearing loss). After the procedures alpha2-macroglobulin decreases by about 58%, fibrinogen by about 69%, IgM by about 61%, LDL-cholesterol by about 77%, apolipoprotein B by about 76% and lipoprotein(a) by about 63%. It corresponds with a decrease in blood and plasma viscosity and clinical improvement in the observed patients, i.e. visual improvement, acceleration of tissue defect healing and improvement in hearing. We noticed 7.1% clinically insignificant side-effects. The method of haemorheopheresis was safe. It led to improvement in patients' clinical condition in the above mentioned indications when other methods of treatment failed.
Keywords: mikrocirkulace; Female; ženské pohlaví; Foot; Peripheral Vascular Diseases; lidé; hyperlipidemie; Plasmapheresis; Recovery of Function; Macular Degeneration; obnova funkce; noha (od hlezna dolů); Middle Aged; Male; vředy na noze (od hlezna dolů); Aged; makulární degenerace; Microcirculation; onemocnění periferních cév; plazmaferéza; lidé středního věku; Foot Ulcer; senioři; mužské pohlaví; Hyperlipidemias; Hearing Loss, Sudden; náhlá nedoslýchavost; Humans